2023
DOI: 10.1002/biot.202300311
|View full text |Cite
|
Sign up to set email alerts
|

Development of heart organoid cryopreservation method through Fe3O4 nanoparticles based nanowarming system

Seul‐Gi Lee,
Jin Kim,
Jin Seok
et al.

Abstract: Beyond single cell two‐dimensional (2D) culture, research on organoids that can mimic human organs is rapidly developing. However, there are still problems in commercialization and joint research using organoids due to the lack of technology to safely store organoids. Since organoids are 3D complex structures with a certain size (0.1 to 5 mm) beyond the size of cells, the conventional cell‐level cryopreservation method using cryoprotectant (CPA) cannot overcome the damage caused by volume change due to osmotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The establishment of cryopreservation and thawing protocols for organoids could enhance biobanking and the utility of organoids in research and therapy. While several studies have investigated cryopreservation methods for 3D cell culture models, no specific protocol has yet been developed for brain organoids [21][22][23][24][25] . The cryopreservation of organoids is influenced by various factors, including mechanical stress, cooling and thawing rates, organoid size, and the type of cryoprotective agents (CPAs).…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of cryopreservation and thawing protocols for organoids could enhance biobanking and the utility of organoids in research and therapy. While several studies have investigated cryopreservation methods for 3D cell culture models, no specific protocol has yet been developed for brain organoids [21][22][23][24][25] . The cryopreservation of organoids is influenced by various factors, including mechanical stress, cooling and thawing rates, organoid size, and the type of cryoprotective agents (CPAs).…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic nano-rewarming has been used for vitrification preservation of cardiac organs. Lee et al [199] demonstrated a successful cryopreservation method for organoids based on a Fe 3 O 4 magnetic nano-rewarming system. It has been verified through heartrate measurement, histological analysis, contraction force analysis, and multielectrode array that magnetic nano-rewarming can significantly improve the functional recovery and survival rate of heart organs after freeze-thaw.…”
Section: Rapid Rewarming Methodsmentioning
confidence: 99%